1992
DOI: 10.1042/bj2810381
|View full text |Cite
|
Sign up to set email alerts
|

The role of pancreatic hormones in the regulation of lipid storage, oxidation and secretion in primary cultures of rat hepatocytes. Short- and long-term effects

Abstract: Exposure of cultured rat hepatocytes to a high concentration of insulin (78 nM) for 24 h in the presence of extracellular oleate (0.75 mM) resulted in a decrease in the secretion of apoprotein B (apoB) and triacylglycerol associated with verylow-density lipoprotein (VLDL). However, continuous exposure of the cells to insulin for longer periods (72 h) stimulated the secretion of apoB and triacylglycerol. Treatment of hepatocytes with glucagon (0.1 zM) for 24 h also suppressed the secretion of VLDL apoB, cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 53 publications
7
41
0
3
Order By: Relevance
“…Although additional action of PI 3-K in later vesicular trafficking cannot be ruled out, there appears to be a requirement for PI 3-K in targeting of apoB for degradation in an early stage of assembly. This is consistent with studies indicating that insulin interferes with the assembly of VLDL as denser apoBcontaining lipoproteins continue to be secreted in the presence of insulin (57). The observation that insulin increases the amount of PI 3-K present in an ER compartment containing apoB suggests that localization of PI 3-K may be important in FIG.…”
Section: Fig 6 Subcellular Localization Of Irs-1⅐pi 3-k Complexes supporting
confidence: 79%
“…Although additional action of PI 3-K in later vesicular trafficking cannot be ruled out, there appears to be a requirement for PI 3-K in targeting of apoB for degradation in an early stage of assembly. This is consistent with studies indicating that insulin interferes with the assembly of VLDL as denser apoBcontaining lipoproteins continue to be secreted in the presence of insulin (57). The observation that insulin increases the amount of PI 3-K present in an ER compartment containing apoB suggests that localization of PI 3-K may be important in FIG.…”
Section: Fig 6 Subcellular Localization Of Irs-1⅐pi 3-k Complexes supporting
confidence: 79%
“…Effects of insulin on synthesis and degradation of apoB and on export of TG as VLDL from hepatocytes are controversial. Some studies conducted using hepatocytes from rats (Beynen et al 1981;Sparks and Sparks 1995;Chirieac et al 2000) support that insulin suppresses hepatic VLDL secretion and apoB synthesis, whereas other studies (Satoh et al 1987;Bjornsson et al 1992) support that insulin enhances TG secretion rate and inhibits apoB degradation. In all these studies, effects of glucagon were shown to be opposite of insulin.…”
Section: Hepatic Lipidosismentioning
confidence: 97%
“…In the case of hypertriglyceridemia, a major contributory factor is increased VLDL secretion by the liver. Many of the above disturbances probably contribute to the overall increase in hepatic VLDL output, including increased influx of nonesterified fatty acids, 28,[43][44][45][46] hepatic insulin resistance, [47][48][49][50][51] and hyperglycemia. [5][6][7][8]44 The precise effects of glucose on VLDL secretion are, however, controversial.…”
Section: Discussion Glucose Increases Hepatic Tag Transport By Increamentioning
confidence: 99%
“…In particular, impairment of the efficient transfer of neutral lipids, especially of TAG, to these crucial intracellular assembly sites may impede the normal production of mature VLDL. 26,27 In addition to that secreted as VLDL, lipid-poor apoBcontaining particles are secreted by perfused rat liver, 65 rat hepatocytes, 39,43,66,67 and the rat hepatoma cell line McA-RH7777 cells. 18,19 It has been suggested that these denser particles are formed during cotranslational assembly, stabilized by the acquisition of a small quantity of lipid 22 and may represent the products of the stage 1 lipid transfer process.…”
Section: Glucose Enhances Predominantly the Bulk Lipidation Step Of Vmentioning
confidence: 99%